Analysis of one way valve mechanism for wings of a flapping drone / Deng Xinchen - Deng, Xinchen (2020)
The flapping drone is one type of MAVs which is defined as a miniature unmanned aerial vehicle that is inspired by flying birds and insects. Flapping wings can make a perfect combination of thrust and lift by flapping up and down with full usage of unsteady air. The flapping drone has the advantages of high maneuverability and a special lift generation mechanism. Compared with rotary-wing or fixed-wing MAV, it is smaller, lighter, and has higher flight performance. It can quickly change the flight direction and flight speed by control the flapping frequency and it is the only flight mode that does not cause a stall. Therefore, flapping drones have great use value and prospects in the military and civilian fields. However, flapping drones have some disadvantages. Its wings only have one degree of freedom which makes it can only flap up and down so that the drag force created by flapping is always equal. This phenomenon affects the flight ability of drones. The primary and secondary feathers of birds can cover and separate from each other. The feathers cover each other to increase the lift during the upstroke of wings and open to create a gap to reduce the drag during the downstroke. According to this mechanism, this research studied the one way valve mechanism to investigate the effects of one way valve on flight performance of flapping drones. There are two parts of this research. The first part used ANSYS software to create several models of one way valve mechanism including single valve and two valves, different air inlets and four types of valve opening angles. Then CFD simulation was used to test the performance of these models. According to the comparison of the results, the conclusion is that the one way valves perform the most effective when the angle of the opening in the range of 30° and 45°. iv The second part used actual experiment to test the one way valve wings. There are four types of wings were designed, produced and tested the flight performance in this research. Four wings were also measured the velocity generated by wings on a test platform. The result of the actual experiment got similar conclusions with CFD simulation which is the one way valve with reasonable layouts on flapping wings can improve the flight capability of flapping drones.